2021
DOI: 10.1186/s12985-021-01698-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and hepatitis B virus among pregnant women in Luanda (Angola): geospatial distribution and its association with socio-demographic and clinical-obstetric determinants

Abstract: Background HIV and HBV infections remain responsible for high rate of morbidity and mortality in many African Countries, affecting women and newborns. This study aims to analyze the spatial pattern of HIV and HBV infections in pregnant women in Luanda, Angola, and the statistical association between HIV and HBV and socio-economic characteristics, hygiene, and health status. Methods Detection of anti-HIV antibodies (total anti-HIV-1, anti-HIV-2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
1
1
1
Order By: Relevance
“…In our study, unemployed people made up more than half the workforce (51.7%), with a predominance of women (43.0% of the total workforce). This result is similar to that of Mossoro-Kpinde in 2016 [5] and Nkuxi in Angola [29]. It is thought to be linked to the feminization of HIV infection in sub-Saharan Africa [27] and to the higher school dropout rate for girls in CAR.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, unemployed people made up more than half the workforce (51.7%), with a predominance of women (43.0% of the total workforce). This result is similar to that of Mossoro-Kpinde in 2016 [5] and Nkuxi in Angola [29]. It is thought to be linked to the feminization of HIV infection in sub-Saharan Africa [27] and to the higher school dropout rate for girls in CAR.…”
Section: Discussionsupporting
confidence: 82%
“…The seroprevalence of hepatitis b and c viruses in this study is higher than that of 6.25% in Ethiopia and 8.1% in the western part of Nigeria This may be attributed to the lower sociocultural status of these women, polygamous marriage practices, cultural practices like tribal marks, and early marriages practices in the setting where this study was conducted (11,12). Also, the seroprevalence of HBV was found to be higher than the findings from studies done in other parts of Nigeria and other LMICs where the seroprevalence ranged from 4.6%-9.7% (11,12,13,14,15,16,17,18,19,20,21,22), but lower than the finding in Angola of 25.7% seroprevalence (23). A similar study in Central Nigeria also found a high prevalence of 19.5% and this may be due to the exclusion of women who had been vaccinated for HBV from the study (24).…”
Section: Discussioncontrasting
confidence: 60%
“…Hepatitis B Virus disease is more prevalent in Sub-Sahara Africa; about 6 to 25 percent Sub Saharan Africans are infected with the disease (15,16). Greater Monrovia region and Liberia has a prevalence of about 2% (17).…”
Section: Introductionmentioning
confidence: 99%